Editorial: further evidence for the use of advanced magnetic resonance imaging techniques to monitor NAFLD – authors' reply. Issue 9 (3rd April 2017) - Lin, S. C.; Loomba, R.
Abstract : Linked Content This article is linked to Mansour and McPherson, and Lin et al papers. To view these articles visithttps://doi.org/10.1111/apt.14005 andhttps://doi.org/10.1111/apt.13951 .